Formative assessment as a learning tool: Enhancing Arabic vocabulary and grammar through interactive evaluation in a non-formal setting - Hamidah, Husnul; Razida, Mirdawati; Qomari, Nur (Asatiza: Jurnal Pendidikan, 2025)
Despite the established theoretical potential of formative assessment, a significant gap exists in understanding its practical application and impact within Arabic language pedagogy, particularly in non-formal educational settings. This study addresses this gap by exploring the role of evaluation tools in enhancing vocabulary and grammar mastery at LKP Kampung Arab Al-Azhar Pare, a non-formal institution in Indonesia. Employing a qualitative descriptive methodology, data were collected through semi-structured interviews with five teachers and twenty students, non-participant observations, and document analysis. The findings reveal a comprehensive typology of evaluation tools, strategically implemented as active pedagogical strategies rather than mere measurement instruments. These tools, which range from digital gamified quizzes (e.g., Kahoot, Wordwall) to collaborative performance tasks, were found to significantly enhance student engagement, foster a deeper conceptual understanding of grammar, and reinforce the functional application of vocabulary. A critical factor in their efficacy was the consistent provision of explanatory, task-focused feedback from teachers. The study concludes that a formative, integrated evaluation system is instrumental in bridging the gap between assessing knowledge and actively cultivating it. This research offers a replicable framework for non-formal institutions and contributes to Arabic language pedagogy by empirically demonstrating how a holistic assessment approach can transform learning processes and outcomes.